DESIGNING AN ENGLISH TEACHING MATERIAL FOR TENTH GRADE STUDENTS OF CULINARY STUDY PROGRAM - Brilianto, Iman; Rezeki, Yanti Sri; Maral, Sofian (FKIP - Universitas Tanjungpura, 2020)
This study was aimed to design a book that can be used as supplementary material to teach English for culinary study program. This study was classified as Research and Development (R&D). The step of conducting this study used ADDIE model with the exclusion of implementation (I) stage and evaluation (E) stage so this study tended to focus on doing three phases only; analyze, design, and develop. The subjects of this research were English teacher and 32 tenth grade students of culinary study program of SMKN 3 Singkawang. The tools for obtaining the data were questionnaires, interview, and internal validation. The result of this study is a course book for culinary study program namely English for Culinary for beginner level. Internal validation was carried out up to two times to have better product.